Education Directors Acting as an Agent for a Transformation: A Case-based Investigation - Rawal, Devendra; Sherchan, Bipin; Baskota, Prateet; Adhikari, Puja (Journal of Durgalaxmi, 2023)
Education is a moral endeavour aimed at improving society. The education directors of the College were supposed to lead the way in implementing the changes by acting ethically. Regretfully, in certain instances, they face criticism for their immoral actions. Thus, this research article aims to investigate how well college education directors function as agents of change in the direction of transformative ethics. Using the interpretivism paradigm and the narrative inquiry approach, the lived narratives produced by four governmental college education directors from three distinct regions of the Bagmati province—Lalitpur, Kathmandu, and Bhaktapur—were purposefully chosen. We used in-depth interviews to determine how administrators felt about the ethical phenomena in light of the developments. Additionally, it shows ethical sensitivity, a fundamental component of a flexible society with sensible people. It implies that treating others with kindness and respect empowers them to consider change. Humanity is the primary source of ethical development, after which everything shifts simultaneously. This discovery clarified the role that ethics plays in bringing about improvements. It disseminates ethical knowledge, values, and expertise throughout the community, college, and individuals.